ANALISIS KEHIDUPAN SISWA MENGEMBANGKAN BUDAYA LOKAL DI LINGKUNGAN SEKOLAH MENENGAH AGAMA KATOLIK (SMAK) BHAKTI LUHUR MALANG - Maria Dara Sintani; Yuliana Eni Yuliati; Fabianus Selatang; Maria Vianti Desa (Jurnal Pelayanan Pastoral, 2021)
Diversity of culture, ethnicity, language is not only a wealth or treasure in living together, but can also threaten unity, harmony and harmony. Conflicts between cultures, ethnicities and languages ​​often occur in social life. This has a negative impact not only on inter-ethnic life, but also on religious life. The purpose of this study is to examine the threat aspect of cultural diversity, as an opportunity to build and strengthen a sense of brotherhood, love for others and uphold mutual respect and respect for differences as the capital of religious and social life by students of SMAK Bhakti Luhur Malang. The method used by the researcher is a qualitative method. The researcher used a descriptive approach. Sources of data are students in grades 1, II and III. The researcher chose 3 students as representatives of the population. In addition, data was also taken from teachers and school principals. The technique of determining the informant uses a purpose sampling technique. Researchers also refer to research results that have been published in national journals in order to map the novelty of this research. The data collection technique is open interview. The instrument used by the researcher was a list of questions. The analysis technique goes through three stages, namely reduction, display and data verification. The author concludes that tensions and conflicts are caused by a lack of understanding and awareness in addressing ethnic, linguistic and cultural differences. The development of local culture in schools as a constructive step in order to develop religious values. Therefore, it is necessary to liven up local cultural values ​​as a living laboratory for students so that they can be used as a basis for developing an attitude of religious moderation in the wider community.